From Cleantech to Cleanweb – The Finnish Cleantech Space in Transition - Annu Kotiranta; Antti-Jussi Tahvanainen; Peter Adriaens; Maria Ritola (The Research Institute of the Finnish Economy (ETLA), 2015)
Now that the worst of the growing pains have been subdued, cleantech has made a respectable comeback onto the global agenda of firms, investors and economic developers alike. One might say it is bigger than ever, with a constantly proliferating range of cleantech companies and business models. In the midst of the resurgence, Finnish CleanTech has been recognized globally. Recent rankings by the WWF (WWF & Cleantech Group (2014): The Global Cleantech Innovation Index 2014) placed Finland in the top-3 of global leaders in cleantech, along with Israel and the US. Against this backdrop, this report takes a closer look at the Finnish commercial cleantech space and scrutinizes it in light of select indicators such as degree of specialization into cleantech, type of industrial activity, generation of value added, financial performance as well as type and volume of intellectual property generated. The results are thought-provoking. Of the many discoveries made in the report, three strike as critical: First, the Finnish cleantech space is dominated by manufacturing-driven businesses. Second, consumer-oriented technical innovations seem to be rare. And third, the engine of industrial renewal – the layer of small and medium-sized firms – seems to struggle with financial sustainability. The ability to shift gears from manufacturing- to service-driven businesses may be compromised if the low financial viability of small and medium -sized companies turns out to be more than a statistical fluke. These firms have been known to possess the rare capability to mock conventional industry boundaries to develop novel business models and open new markets. Poor commercial performance would indeed be bad news for the long-term development of the cleantech space in Finland. To solidify these results, uncover the reasons behind them, and identify opportunities going forward, however, more in-depth inquiries need to be made. In the gold rush era of digitalization, our findings beg the question whether the seemingly dominant focus on manufacturing, engineering and technology could become the ball-and-chain to the growth of Finnish cleantech. Digitalization is currently revolutionizing service businesses and providing opportunities to harness vast consumer markets for rapid, scalable growth – particularly in the area of resource efficiency – via new, often disruptive business models. In recent years these opportunities have been widely discussed in several contexts including cleanweb, smart cities, internet of things, and consumer cleantech. Should the Finnish cleantech industry do what the Finns have always done best and stick to the development of cutting-edge technological solutions? Or should Finnish companies adopt service-based business models that have allowed other countries (notably the US) to transition to the digital age of cleantech?
Keywords: L16; O12; O14; O52; 330; Cleantech; Cleanweb; Industrial renewal; Digitalization; Statistics; Finnish economy; Umwelttechnik; Branchenentwicklung; Computerunterstützung; Finnland